The Effect of Compensation and Competence on Employee Performance at Bank BJB Branch - Ery Rosmawaty Rosmawaty; Wike Pertiwi (International Journal of Ecma Science, 2021)
The purpose of this study was to determine: (1) the effect of compensation on employee performance at Bank BJB Branch Brass, (2) the effect of competence on the performance of employees at Bank BJB Branch Brass, and (3) the influence of compensation and competency on the performance of employees at Bank BJB Branch Brass, this research uses explanatory research with a quantitative approach. The population of this study is employees of Bank BJB Branch Brass with a population of 54 respondents. Data were collected by questionnaires that have been tested for validity and reliability. The data analysis technique used is multiple regression. As for the data processing using the program SPSS version 20 for Windows. The results showed that: (1) compensation effect on employee performance is evidenced by the beta coefficient equal to (β) equal to 0.323; (2) competence influence on employee performance is evidenced by the beta coefficient (β) of 0.641. Also seen from count variable compensation and competency that is greater than the value table and significant value which is much smaller than 0.05. And (3) compensation and competency together (simultaneously) affect the performance of employees at Bank BJB Branch Brass, seen from the value of F of the two independent variables is greater than the value of F table (40.694 3.179) with a probability smaller than 0.05 (0.000 0.05). The results of the coefficient number Adjust R Square were obtained at 0.615. This means that compensation and competency have an influence on the rise and fall of the performance of employees by 61.5%. While the remaining 38.5% are caused by other factors not analyzed in the models used in the study.